A Review on Phytochemistry and Pharmacology of Otostegia persica (Burm.f.) Boiss. - J Asgarpanah; S Mohammadi Motamed (Institue of Medicinal Plants, ACECR, 2013)
Iran has a great wealth of various naturally occurring medicinal plants which have great potential pharmacological activities. Otostegia persica (Burm.f.) Boiss. is one of these plants which is a perennial shrub found in South and Southeast of Iran. The aerial parts of O. persica have been used in Iranian traditional medicine to treat various types of diseases (e.g., inflammatoryand pain-mediated diseases, malaria and diabetes). Research carried out using different in vivo and in vitro assays of biological evaluation support most of these claims. The active pharmacological components of O. persica most studied are flavonoids and terpenoids. This paper presents the traditional uses, botany, phytochemistry, and pharmacology of this medicinal plant. This is the first article reported in this review form about O. persica which might be helpful for scientists and researchers to find out new in modern health concept.